(3GdJRGe GdHGFY HGYdGe GdeTJQi hJHUjQg ai GdeQMdI GdSGHbI Ydi GHQGe GdHjY (B/ s - (3QeVGf GdebWha YeQ YHO Gddg s; (3LGHQ eMLhH Ydi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2012)
(3JfGhdJ gPI GdOQGSI GdJRGe GdHGFY HGYdGe GdeTJQi hJHUjQg ai GdeQMdI GdSGHbI Ydi GHQGe GdHjY hfXQG dGgejI GdehVhY Ydi GdeSJhjjf GdYdei hGdYedi hdGSjeG ai YbO GdHjY heG jJHYg ef GTcGdGJ LGAJ gPg GdOQGSI dJhVjM eGgjI GdGdJRGe hGKGQg hJWhQg hOQGSI GdfUhU hGdGLJgGO GdbVGFi ai gPG GdehVhY hef NdGd GdOQGSI fQi Gf JbOje GdMeGjI ddeSJgdc jSJdRe aQV GdJRGe Ydi YGJb GdefJL hGdUGfY hGdehRY HGYdGe GdeSJgdc HcGaI GdHjGfGJ hGdeYdheGJ hcPdc GdehGUaGJ GdeJYdbI HGdeHjY dJfhjQ GQGOJg hGNJjGQ GdSdYI GdefGSHI dXQhag hGecGfjGJI hjVGM hLhg GdNWhQI hGdGMJjGWGJ GdhGLH GJNGPgG ajeG jJYdb HGSJNOGegG HMjK jbOe Ydi GHQGe GdYbO HGOGQI MQI eSJfjQIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI , cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2012.s
(3HHdjhLQGajG(B: (3UaMGJ (B301-318.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3YbO GdHjYs; (3EYdGe GdeSJgdcs; (3GdGdJRGe HGdEYdGes; (3GdWHjYI GdbGfhfjI ddEdJRGe HGdEYdGe s; (3CMcGe GdEdJRGe HGdEYdGes; (3EKHGJ GdEdJRGe s; (3EYdGe GdeTJQjs; (3GdYOGdI GdYbOjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs